RESPON MASYARAKAT TERHADAP PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KELURAHAN PARDAMEAN KECAMATAN SIANTAR MARIHAT KOTA PEMATANGSIANTAR - Atika, Tuti; Tambunan, Novriani (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Poverty is a condition or condition of the inability of individuals or groups of people to meet the necessities of life, both physical and economic conditions. In an effort to eradicate poverty, improve welfare and increase people's access to food, through a social assistance program called the BPNT Program. In the running of the Non-Cash Food Assistance program, of course, it raises various responses from the beneficiary community. This study measures response through 3 indicators, namely perception, attitude, and participation. This research is classified as a descriptive research type. The population in this study were pure beneficiaries of the BPNT program with a sample of 77 respondents. The data analysis technique uses a single table which is explained descriptively and statistical analysis of the Chi Suare test. Based on data analysis, it can be concluded that the BPNT Program in Pardamean Village, Siantar Marihat District, Pematangsiantar City received a positive response with a value of 0.55 through the overall results of the three variables namely perception, attitude and participation. The results of the Chi Square test show that there are differences in responses based on age level towards community participation, between education level and community understanding, and the number of dependents on understanding and attitudes of the BPNT recipient community. Meanwhile, the variable types of work, income, and housing status had no effect on differences in community responses. It is hoped that the BPNT program can continue and be further improved, both in terms of implementation and outreach, so that the community can experience more benefits and a better positive impact on the Beneficiary Families.